PENGARUH MARKETING KNOWLEDGE MANAGEMENT TERHADAP BISNIS PERFORMANCE YANG DIMEDIASI OLEH PRODUK INNOVASI DAN DIGITAL MARKETING PADA PENGGUNA PRODUK CAMILLE BEAUTY - Amanda Oktavia Amielia; Sidiq Permono Nugroho (POLITEKNIK LP3I JAKARTA, 2024)
The purpose of this study was to analyze the effect of marketing knowledge management on business performance mediated by product innovation and digital marketing on users of camille beauty products. This research method is quantitative. The population in this study were students who used camille beauty products in Surakarta. The number of samples in this study were 95 respondents. The sampling technique can be classified as non-probability with purposive sampling. The data used in this research is primary data. The data collection method used in this research is by distributing questionnaires. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The results of this study are that Marketing knowledge management has a significant positive effect on business performance. Marketing knowledge management has a significant positive effect on product innovation. Marketing knowledge management has a significant positive effect on digital marketing. Product innovation has a significant positive effect on business performance. Digital marketing has a significant positive effect on business performance. Marketing knowledge management influences business performance mediated by product innovation. Marketing knowledge management affects business performance mediated by digital marketing. Keywords: Marketing Knowledge Management, Business Performance, Product Innovation, Digital Marketing.